Physical Stability and Antioxidant Peel-Off Kefir Mask Arachi (Arachis Hypogaea L) - Khairunnisa, Amalia; Kartinah, Nani; Viogenta, Pratika; Mulia, Mulia (Universitas Ahmad Dahlan, 2025)
The fermented product sector can produce kefir for use in cosmetic preparations. Kefir has weak storage stability and strong antioxidant properties, making it a suitable raw material for cosmetic formulations. The purpose of this study is to determine the best concentration of peanut kefir in Peel-off mask Arachi through antioxidant activity and physical stability during seven cycles of room temperature storage and freeze-thaw (4±2ºC and 40±2ºC). Using the DPPH method based on the IC50 value, the antioxidant activity test was conducted. It was retested after 7 cycles or 28 days. At ambient temperature and freeze-thaw temperature, organoleptic tests, pH, adhesion, and spreadability were conducted in cycles ranging from 0 to 7. The peel-off kefir mask preparations with F1 (0.5%), F2 (1%), and F3 (2%), concentrations created a homogeneous, viscous preparation that was stable at room temperature and freeze-thaw stable for seven cycles, according to the results. In terms of the pH test, the sample showed a drop in pH following storage, stable adhesion for up to seven cycles. However, for F1, the adhesion was not stable in either scenario. With a significant activity category, the formula's antioxidant activity also declines in IC50 values. Therefore, it can be said that even though the peel-off mask preparation changed after storage in a few different ways, it still falls short of the threshold in terms of the physical characteristics of the cosmetic preparation.